Anterior Hippocampal–Cortical Functional Connectivity Distinguishes Antipsychotic Naïve First-Episode Psychosis Patients From Controls and May Predict Response to Second-Generation Antipsychotic Treatment. (21st August 2019) - Blessing, Esther M; Murty, Vishnu P; Zeng, Botao; Wang, Jijun; Davachi, Lila; Goff, Donald C
Abstract: Background: Converging evidence implicates the anterior hippocampus in the proximal pathophysiology of schizophrenia. Although resting state functional connectivity (FC) holds promise for characterizing anterior hippocampal circuit abnormalities and their relationship to treatment response, this technique has not yet been used in first-episode psychosis (FEP) patients in a manner that distinguishes the anterior from posterior hippocampus. Methods: We used masked-hippocampal-group-independent component analysis with dual regression to contrast subregional hippocampal–whole brain FC between healthy controls (HCs) and antipsychotic naïve FEP patients ( N = 61, 36 female). In a subsample of FEP patients ( N = 27, 15 female), we repeated this analysis following 8 weeks of second-generation antipsychotic treatment and explored whether baseline FC predicted treatment response using random forest. Results: Relative to HC, untreated FEP subjects displayed reproducibly lower FC between the left anteromedial hippocampus and cortical regions including the anterior cingulate and insular cortex ( P < .05, corrected). Anteromedial hippocampal FC increased in FEP patients following treatment ( P < .005), and no longer differed from HC. Random forest analysis showed baseline anteromedial hippocampal FC with four brain regions, namely the insular–opercular cortex, superior frontal gyrus, precentral gyrus, and postcentral gyrus predicted treatment response (area under the curve = 0.95). Conclusions: Antipsychotic naïve FEP is associated with lower FC between the anterior hippocampus and cortical regions previously implicated in schizophrenia. Preliminary analysis suggests that random forest models based on hippocampal FC may predict treatment response in FEP patients, and hence could be a useful biomarker for treatment development.